Ready-to-eat food consumption practices, food safety knowledge and relation to gender and education level of consumers in Kuala Lumpur, Malaysia - A.c.s., Anusha; R., Tunung; C., Kavita; A., Ribka (Rynnye Lyan Resources, 2020)
This study was aimed to evaluate consumers’ consumption practices of ready-to-eat (RTE) foods, food safety knowledge, and the relationship to gender and education level. A total of 258 consumers in Klang Valley, Kuala Lumpur, Malaysia were given questionnaires through convenience sampling. The results showed that the biggest motivation for consumers in purchasing RTE foods was convenience (47.3%). 40.7% of respondents purchase RTE foods more than twice a week, and 36.8% of respondents consumed RTE food at restaurants and cafes. A total of 54.3% of the respondents purchased RTE foods for lunch, and 48.1% of respondents usually spend RM11-RM20 per person. About 81% of respondents knew that the common symptom of foodborne disease is diarrhea, and 42.2% of respondents knew about the correct temperature for refrigeration. Most of the respondents (66.7%) knew that room temperature encourages the multiplication of bacteria, and 36.4% of respondents knew that bacteria will grow quickly at body temperature. About 60.9% of respondents knew that raw and cooked food should be separated to prevent the transfer of bacteria, and 62% of the respondents knew that placing raw meat in the plastic bag before putting it into the grocery basket decreases the chance of foodborne illness. However, only 10.1% of the respondents knew that the best way to clean a cutting board after using it for raw meat is by washing with bleach and water. Female respondents and those with higher education level generally had better food safety knowledge. This study could benefit RTE food marketers in gaining better insights into consumers’ behavior patterns towards RTE food. This study could also contribute to knowing the baseline knowledge of consumers in food safety as it is essential for the development of effective health educational programmes.